Substrates and irrigation levels for growing desert rose in pots - Colombo,Ronan Carlos (2018)
ABSTRACT In the past decades, desert rose has become a very popular ornamental plant, especially among collectors, due to its exotic and sculptural forms. However, it has been grown on a commercial scale only recently, and little is known about how to best manage it as a container-grown plant, or even which potting medium (substrate) to recommend. Therefore, the aim of this study was to investigate the interactions between potting media and irrigation levels for growing desert rose as a potted ornamental plant. The experiment was conducted in a greenhouse using a 6 x 2 factorial arrangement with six replications, six potting media and two irrigation levels. The mixes were characterized by measuring their physical properties, specifically the density and water retention capacity (WRC), as well as chemical properties, such as the pH and electrical conductivity (EC). After 210 days, plant growth and plant water consumption were evaluated and measured. A lower dry density for the vermiculite mixes was observed in comparison to that for the sand mixes. However, WRC ranged from 428 to 528 mL L-1 among the mixes, values considered close to ideal. In general, plant growth exhibited higher increases in mixes consisting of coconut fiber + sand or vermiculite, regardless of the irrigation level. Mixes of vermiculite + coconut fiber and sand + coconut fiber can be used to grow desert rose in pots, as long as irrigation is used to maintain the moisture content of the potting medium (mix) between 60-70% and 80-90% of the WRC.